The Effect Of Supervision And Work Discipline On Employee Performance At The General Criminal Investigation Directorate Office Of The Bengkulu Provincial Police - Dewa, Bara Calang; Herlina, Yeni; Irwanto, Tito; Putra, Iswidana Utama (Jurnal Pakar Manajemen, 2026)
The purpose of this study is to determine the effect of supervision and work discipline on the performance of employees at the Bengkulu Regional Police Criminal Investigation Directorate. The population in this study consisted of all 112 employees at the Bengkulu Regional Police Criminal Investigation Directorate, with a sample size of 112 employees. The sampling technique used was cluster sampling. The data analysis technique used multiple linear regression: Y = 23.319+0.166X1+0.015X2, meaning that if supervision and work discipline are increased by 100%, employee performance will be 0.166 and 0.015, respectively. The results of the study show that by comparing the Fcount value with the Ftable value, it is known that the Ftable value is 3.757 > 3.16 and it can be concluded that supervision and work discipline have a significant effect on employee performance at the Bengkulu Regional Police Criminal Investigation Directorate Office. Based on the partial test, it is known that supervision has a positive and significant effect on the performance of employees at the Bengkulu Regional Police Headquarters' General Criminal Investigation Directorate with a sig value of 0.004 < alpha (0.05), while work discipline has a positive and insignificant effect on the performance of the Bengkulu Regional Police Headquarters' General Criminal Investigation Directorate with a sig value of 0.810 > alpha (0.05)